HYDROTHERMAL PROCESS FOR GROWING OPTICAL-QUALITY SINGLE CRYSTALS - FERRETTI; AUGUST; GIER; THURMAN E (1991)
A hydrothermal process for growing a crystal of MTiOXO4 at an elevated temperature is disclosed which employs a growth medium comprising a mineralizer solution, and is characterized as employing aqeuous mineralizer solution in which the concentration of M is at least about 8 molar, and as employing a growth region temperature of less than about 500 DEG C. and/or a pressure of less than 14,000 psi during crystallization. M is selected from the group consisting of K, Rb, Tl and NH4 and mixtures thereof, and X is selected from the group consisting of P and As and mixtures thereof.